A policy review of Basic Income for the Arts Pilot Scheme - O'Brien, John; Clancy, Annette (Irish Journal of Arts Management and Cultural Policy, 2022)
The launch of Basic Income for the Arts in April 2022 by the Irish Government marks a significant moment for the arts in Ireland. This article addresses the key assumptions underlying the policy and discusses whether what is primarily a welfare state redistributive intervention will address the social and economic complexities of life within the cultural and creative economy in Ireland.